39 Improving communication experiences for hospitalised children and adolescents with learning disabilities/autism. (15th December 2021) - Garcia-Rodriguez, Ruth; Craven, Sophie; Gnoiska-Rapala, Weronika; Rogers, Jennifer
Abstract : Background: Hospitals can be stressful environments for children and young people (CYP). CYP with Learning disabilities (LD) and Autism (ASD) experience a higher rate of comorbid health conditions, increased risk of psychiatric morbidity (Muskat 2017), higher rates of hospitalisation and longer length of stay (Oulton 2018). Behaviours that challenge are frequently used by this group during hospitalizations due to environmental and communication difficulties. A recent staff survey highlighted staff perceived difficulties working with this group – identifying a need for further training in specialised communication skills and better understanding of LD/ASD needs and how to meet them. Our aim was to empower staff with additional knowledge and communication skills, which would subsequently improve the experiences of CYP with LD/ASD and their families during their stay at Great Ormond Street Hospital (GOSH). Methods: 3 short videos and a recorded teaching session were created by staff from GOSH LD and SCDC teams. The videos were designed to signpost staff to relevant resources available in GOSH and provide guidance around their effective use. The recorded teaching session was aimed at improving staff confidence in their knowledge and management of this group, addressing current barriers, and a better understanding of behaviours that challenge in this population. The short videos were disseminated to the Practice Educators of 4 wards: Squirrel, Sky, Koala and Starfish to be used in educational sessions. The recorded teaching session will be available on the new GOSH digital environment (DEN). Results: Preliminary results show a positive response from ward staff. Most responses found the training useful. The materials were found to be useful and helpful in improving staff communication with this group. Discussion: Using bespoke materials as an educational tool can be an effective method to improve communication with CYP with LD/Autism.